Fibre Bragg grating sensor system for temperature application - Suzairi, Daud; Ahmad Noorden, Ahmad Fakhrurrazi (UTM Press, 2016)
A practical pass-through type fibre Bragg grating (FBG) temperature sensor system have been designed and experimentally investigated. The performance of FBG was evaluated with the varying of focusing elements in harsh environments, under direct sunlight. The sensor head of FBG was designed to be focused with convex and hand lens. Results shows that the Bragg wavelength shift, ∆ increase proportionally with the temperature for both systems. The sensitivities of FBG were recorded to be 0.0107 and 0.0122 nm °C-1 for the system where convex and hand lens applied to the FBG’s sensor head respectively